Philosophical analysis of radical (critical) pedagogy essential characteristics - Кошетар, У. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2017)
The article is devoted to the philosophical analysis of the basic ideas of radical pedagogy, which is an important component of the modern education of the Information society. The paradigm of defining of critical thinking, proposed by P. Freire, is actualized. The need to review the idea of competence within the framework of philosophical discourse is actualized. The need to consider the idea of competence within the framework of philosophical discourse is actualized.